2018
DOI: 10.1002/chem.201802052
|View full text |Cite
|
Sign up to set email alerts
|

Protein‐Assisted Formation and Stabilization of Catalytically Active Polyoxometalate Species

Abstract: The effect of the protein environment on the formation and stabilization of an elusive catalytically active polyoxometalate (POM) species, K [Hf(α -P W O )] (1), is reported. In the co-crystal of hen egg-white lysozyme (HEWL) with 1, the catalytically active monomeric species is observed, originating from the dimeric 1:2 POM form, while it is intrinsically unstable under physiological pH conditions. The protein-assisted dissociation of the dimeric POM was rationalized by means of DFT calculations. The dissocia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
102
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 48 publications
(122 citation statements)
references
References 85 publications
17
102
1
Order By: Relevance
“…By analyzing the refined co‐crystal structures (Table ), a clear side‐by‐side comparison of POM‐HEWL interaction sites could be made. Similarly to the previously reported structures of HEWL with Zr IV ‐Keggin and Hf IV ‐Wells–Dawson POMs, three distinct interaction sites were observed in all crystals (Figure ) , . Each interaction site consists of two slightly different POM binding modes with HEWL, due to its aforementioned special position in the crystal (Figure ).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…By analyzing the refined co‐crystal structures (Table ), a clear side‐by‐side comparison of POM‐HEWL interaction sites could be made. Similarly to the previously reported structures of HEWL with Zr IV ‐Keggin and Hf IV ‐Wells–Dawson POMs, three distinct interaction sites were observed in all crystals (Figure ) , . Each interaction site consists of two slightly different POM binding modes with HEWL, due to its aforementioned special position in the crystal (Figure ).…”
Section: Resultssupporting
confidence: 82%
“…HEWL was mixed with four Wells–Dawson type POMs: a dimeric [Zr IV (α 2 ‐P 2 W 17 O 61 ) 2 ] 16– and three monomeric POMs [Co II (α 2 ‐P 2 W 17 O 61 )] 10– ( 2 ), [Ni II (α 2 ‐P 2 W 17 O 61 )] 10– ( 3 ) and [Cu II (α 2 ‐P 2 W 17 O 61 )] 10– ( 4 ), resulting in four structural models. Similarly to previously observed,, during the crystallization process the dimeric 1:2 Zr IV ‐Wells–Dawson POM dissociated into monomeric 1:1 Zr IV ‐Wells–Dawson anion [Zr IV (α 2 ‐P 2 W 17 O 61 )] 8– ( 1 ) (Scheme ), which crystalized in a noncovalent complex with HEWL.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The X-ray structures of the complexeso fH EWL with 1:1Z r-K and 1:1H f-WD POMs [34] as well as MD simulations [22] showed that metal-substituted POMs prefer to bind to the protein by pointingtheir catalytically activemetal centers towards the solvent due to the hydrophilicity of the catalytically active M-(OH 2 ) n site. Consequently, the dynamic hydrolysis process should involver eorientation of the POM, in order to bind a backbonea mide oxygen atom (required for the electrophilic activation of the peptideb ond), with the corresponding energy penalty.Ap ossible mono-or bidentatec oordination of the Asp COO À group to the active metal of the POM can, in principle, compensate to some extent for the energy loss due to the POM reorientation and eventual migration from the optimal binding site on the protein surface.…”
Section: Binding Propertiesmentioning
confidence: 98%
“…The results obtained by docking are in line with previous experimental studies on protein-POM systems showing that cleavages ites are often located in the vicinity of the binding sites. [34] Elucidating the molecularo rigins of AspÀXselectivity of Zr-POMs…”
Section: Interaction Between 2:2z R-k Pom and Hbmentioning
confidence: 99%